TWSC at Forty: Multidisciplinary Research and the Challenges to the Center - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2018)
Notes from the editor on this special issue on the commemoration of the fortieth anniversary of the University of the Philippines Third World Studies Center.